2018
DOI: 10.1007/s10664-018-9641-6
|View full text |Cite
|
Sign up to set email alerts
|

Empowering OCL research: a large-scale corpus of open-source data from GitHub

Abstract: Model-driven engineering (MDE) enables the rise in abstraction during development in software and system design. In particular, meta-models become a central artifact in the process, and are supported by various other artifacts such as editors and transformation. In order to define constraints, invariants, and queries on model-driven artifacts, a generic language has been developed: the Object Constraint Language (OCL). In literature, many studies into OCL have been performed on small collections of data, mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…They observed that such benchmarks would encourage the development of new OCL tools. Similar repositories have since appeared in (Noten et al 2017;Mengerink et al 2019).…”
Section: Related Workmentioning
confidence: 96%
“…They observed that such benchmarks would encourage the development of new OCL tools. Similar repositories have since appeared in (Noten et al 2017;Mengerink et al 2019).…”
Section: Related Workmentioning
confidence: 96%
“…Although the meta-models are not labelled, it comes with an analysis tool chain to facilitate experiments. A large dataset of OCL expressions is contributed in [37]. The goal is to enhance OCL-related research, which is demonstrated by replicating several studies about OCL with the dataset.…”
Section: Datasetsmentioning
confidence: 99%